Case Report: Prenatal Genetic Counseling to Parents of Fetuses Suspected of Having Ambiguous Genitalia - Sato, Takeshi; Ishii, Tomohiro; Yamaguchi, Yu; Ichihashi, Yosuke; Ochiai, Daigo; Asanuma, Hiroshi; Kuroda, Tatsuo; Hasegawa, Tomonobu (Frontiers in Pediatrics, 2021)
The occurrence of fetuses suspected of having ambiguous genitalia will likely increase in the future. Currently, the impact of prenatal genetic counseling on the parents’ understanding and psychological preparedness has not been addressed. We provided prenatal genetic counseling to parents of two fetuses suspected of ambiguous genitalia. Case 1: At 22 weeks of gestation, swelling of labia majora, and a clitoris-like structure were noted despite 46,XY detected in amniotic fluid cells. Case 2: At 28 weeks of gestation, bladder exstrophy and a scrotum-like structure were noted. At 32 weeks (Case 1), and 37 weeks (Case 2) of gestation, we shared information with parents regarding the possible difficulty of legal sex assignment at birth, and a scenario for registration of the birth certificate. At birth, both babies presented with ambiguous genitalia. For both cases, the parents remained calm on seeing their baby’s genitalia for the first time. In a month, we shared medical information with parents, including karyotype, testosterone production capacity, and surgical schedule. In both cases parents assigned their respective baby’s legal sex as male. Several months later, parents were questioned on prenatal genetic counseling: Case 1: Mother, “I was prepared to address our baby’s genitalia calmly.” Father, “I understood the procedure of legal sex assignment.” Case 2: Mother, “Without counseling, I would have been more upset and worried.” Father, “We were assured that multidisciplinary experts would support us.” Prenatal genetic counseling provides reassurance to parents, who remain informed and emotionally secure throughout the legal sex assignment of their child.